Neuroprotective effects of different frequency preconditioning exercise on neuronal apoptosis after focal brain ischemia in rats. (3rd June 2019) - Terashi, Takuto; Otsuka, Shotaro; Takada, Seiya; Nakanishi, Kazuki; Ueda, Koki; Sumizono, Megumi; Kikuchi, Kiyoshi; Sakakima, Harutoshi
ABSTRACT: Objective : Preconditioning exercise can exert neuroprotective effects after stroke; however, the effects of exercise intensity, frequency, duration are unknown. We investigated the neuroprotective effect of different frequency preconditioning exercise on neuronal apoptosis after cerebral ischemia in rats. Methods : Rats were divided into the following five groups: 5 times a week of exercise (5/w-Ex) group, 3 times a week of exercise (3/w-Ex) group, once a week of exercise (1/w-Ex) group, no exercise (No-Ex) group, and intact control (control) group. Rats were made to run on a treadmill for 30 min per day at a speed of 25 m/min for 3 weeks. After the running program, the rats were subjected to 60-min left middle cerebral artery occlusion. Two days after ischemia, the cerebral infarct volume, neurological and motor function, Bcl-2-associated X protein (Bax)/B-cell lymphoma 2 (Bcl-2) ratio, expression of caspase-3, and TUNEL positive cells were examined in the cerebral cortex surrounding the ischemic zone. Results : The 3/w-Ex and 5/w-Ex groups showed significantly reduced infarct volumes compared with the No-Ex group, but the 1/w-Ex group did not. In addition, the 3/w-Ex and 5/w-Ex groups had improved neurological scores and sensorimotor function compared with the No-Ex group. The Bax/Bcl-2 ratio, expression of caspase-3, and TUNEL-positive cells significantly decreased in the penumbra area in the 3/w-Ex or 5/w-Ex groups compared with the No-Ex group. Discussion : Our findings suggested that three times or more per week of high-intensity preconditioning exercise exert neuroprotective effects through the downregulation of the Bax/Bcl-2 ratio and caspase-3 activation after stroke. Abbreviations : TUNEL: terminal deoxynucleotidyl transferase-mediated biotinylated dUTP nick and labeling; MCAO:middle cerebral artery occlusion; BAX:Bcl-2-associated X protein; Bcl-2: B-cell lymphoma 2; TTC: 2, 3, 5-triphenyltetrazorlium chloride